Perencanaan Sistem Penyaliran dan Pemompaan pada Tambang Terbuka di PT X Desa Tegalega, Kecamatan Cigudeg Kabupaten Bogor, Provinsi Jawa Barat - Mutiara Nur Fajryanti; Elfida Moralista (Jurnal Riset Teknik Pertambangan, 2021)
Abstract. PT X is a mining company with open pit mining methods for andesite rocks. The implementation of open pit methods is inseparable from the problem of inclusion water of rainfall and groundwater seepage into the mining area (pit). This can lead to disruption of mining activities if not handled properly. In this case to cope with the incoming water at Pit in PT X requires some study. It deals with the large number of pumps needed to tackle the incoming water each day.The purpose of the research is to overcome the potential of water entering the Pit, by making diversion channels and to overcome water that already inside the Pit is handled by making sump and pumping system.The data used are 2014-2018 rainfall data, topographic maps, mine progress maps, land use maps, water velocity data, temperature and humidity data and soil condition and land conservation data. Pit has 4 Catchment Areas with each divided into 3 namely Catchment Area PIT, Catchment Area A, Catcthment Area B, Catcthment Area C with a total area of 26,28 Ha. The water runoff plan during the 10 years period. From these data the reults obtained amounted to 50,35 m3/day. Water discharge that enters from inside and outside the pit with a total discharge of 0,94 m3 /sec. Based on data that obtained the ways to prevent water entering the mining area can be minimized by creating a diversion channel. The first diversion channel made for prevent water entering the mining area that comes from Catchment Area A, the diversion channel made along 569 m from 300–270 mals. The second one made for prevent water from Catchment Area C with total length 756 m from 290–130 mals. So that the incoming water debit becomes as much as 0,53 m3/sec. Sump is place at an elevation 115 masl, volume of sump is 7.900 m3 with dimensions of surface length 43 m, surface width 50 m, the base length of the is 36 m, and the depth of 4 meters can accommodate the total volume of water. The pump used is a MFC 180 , with a total of 2 unit pump, the pumping hours are adjusted based on the incoming water debit per month. The highest pumping hour in November was 15.2 hours with a debit of 12,403.63 m3 / day and the lowest in May was 6 hours with a discharge of 4,896.17 m3 / day. Abstrak. PT X merupakan salah satu perusahaan pertambangan dengan menggunakan Sistem Tambang Terbuka dengan tipe Quarry untuk batuan andesit. Akan tetapi belum tersedianya sistem penyaliran tambang menyebabkan terjadinya banjir pada lokasi penambangan, sehingga mengganggu kegiatan penambangan terutama pada musim penghujan. Tujuan dilakukan penelitian adalah untuk menanggulangi potensi air yang masuk ke pit , maka dilakukan penanggulangan air dari luar pit dengan membuat saluran pengalihan dan penanggulangan air yang masuk ke dalam pit dengan sistem pemompaan dan kolam penampungan.Data yang digunakan merupakan data curah hujan tahun 2014-2018, peta topografi, peta kemajuan tambang, peta tataguna lahan, data kecepatan air, suhu dan kelembaban dan data kondisi tanah dan konservasi lahan. Pit memiliki 4 Catchment Area dengan masing-masing dibagi menjadi 4 yaitu Catchment Area PIT, Catchment Area A, Catchment Area B, Catchment Area C dengan total luasan sebesar 26,28 Ha. Curah hujan rencana dengan data curah hujan selama 10 tahun periode 2014-2018. Hasilnya adalah curah hujan rencana maksimum sebesar 50,35 mm/hari. Debit air yang masuk adalah dari dalam pit dan luar pit dengan total debit sebanyak 0,94 m3/detik. Dari hasil penelitian, saluran pengalihan dibuat pada dua lokasi yaitu untuk menangani Catchment Area A dengan total panjang saluran 569 m pada elevasi 300 -270 dan untuk menangani Catchment Area C dengan panjang 756 m pada elevasi 290 - 130. Sehingga debit air yang masuk menjadi sebanyak 0,53 m3/detik.Kolam penampungan dibuat dengan volume 7.900 m3,dengan dimensi panjang atas 43 dan panjang bawah 36 m, dengan lebar 50 m dan ketinggian 4 m. Pompa yang digunakan adalah 2 unit pompa Multiflow 180 dengan jam pemompaan disesuaikan berdasarkan debit air yang masuk perbulannya. Jam pemompaan tertinggi pada bulan November yaitu 15,2 jam dengan debit 12.403,63 m3/hari dan yang paling rendah pada bulan Mei yaitu 6 jam dengan debit 4.896,17 m3/hari.